Advances in batteries for medium- and large- scale energy storage - Menictas, Chris; Skyllas-Kazacos, Maria; Lim, Tuti Mariana (Woodhead Publishing in energy ;, 2015)
As energy produced from renewable sources is increasingly integrated into the electricity grid, interest in energy storage technologies for grid stabilisation is growing. This book reviews advances in battery technologies and applications for medium and large-scale energy storage. Chapters address advances in nickel, sodium and lithium-based batteries. Other chapters review other emerging battery technologies such as metal-air batteries and flow batteries. The final section of the book discuses design considerations and applications of batteries in remote locations and for grid-scale storage. R.